Design for tomorrow proceedings of ICoRD 2021 - Chakrabarti, Amaresh; Poovaiah, Ravi; Bokil, Prasad; Kant, Vivek (Springer, 2021)
Design For Tomorrow showcases cutting-edge research papers from the 8th International Conference on Research into Design (ICoRD 2021) written by eminent researchers from across the world on design processes, technologies, methods and tools, and their impact on innovation, for supporting design for a connected world.